Attitudes of teachers towards the usage of computers and information technology in education / Wan Yonsharlinawati Wan Jaafar - Wan Jaafar, Wan Yonsharlinawati (2004)
The purpose of this study is to investigate teachers' attitudes towards the usage of computers and information technology in education. The aim of this study is to find out whether school teachers are anxious about computers and information technology. This study also aims to investigate the relationship between availability of personal computers, course attendance and computer anxiety and also to investigate the relationship between availability of personal computers, course attendance and the usage of computers and information technology in the classroom. The subjects of this study are 50 school teachers in Sekolah Menengah Kuala Krai, Kelantan, of whom 17 were male and 33 female. The data were analyzed using descriptive statistics. The results of this study revealed that more than 50 percent of school teachers have a positive attitude towards computers and information technology in the education process. The other significant finding of this study is that many teachers, despite their positive attitude, do not prefer to use technology and computers in the classroom. Over half of the respondents, 56 percent, believe that without a computer in the classroom their teaching is still effective. Furthermore, 28 percent of the respondents also believe that computers should be used for certain subjects only. The results suggest that in general, factors like the availability of personal computers and attending courses do not affect teachers' attitudes. The respondents do not, for example, believe that computers threaten the relationship between teachers and students and they believe that computers and technology help slow learners. Based on the findings, several implications and recommendations are discussed.